DigBody®: A new 3D modeling tool for nasal virtual surgery. (1st July 2018) - Burgos, M.A.; Sanmiguel-Rojas, E.; Singh, Narinder; Esteban-Ortega, F.
Abstract: Background and purpose: Recent studies have demonstrated that a significant number of surgical procedures for nasal airway obstruction (NAO) have a high rate of surgical failure. In part, this problem is due to the lack of reliable objective clinical parameters to aid surgeons during preoperative planning. Modeling tools that allow virtual surgery to be performed do exist, but all require direct manipulation of computed tomography (CT) or magnetic resonance imaging (MRI) data. Specialists in Rhinology have criticized these tools for their complex user interface, and have requested more intuitive, user-friendly and powerful software to make virtual surgery more accessible and realistic. In this paper we present a new virtual surgery software tool, DigBody ® . Methods: This new surgery module is integrated into the computational fluid dynamics (CFD) program MeComLand ®, which was developed exclusively to analyze nasal airflow. DigBody ® works directly with a 3D nasal model that mimics real surgery. Furthermore, this surgery module permits direct assessment of the operated cavity following virtual surgery by CFD simulation. Results: The effectiveness of DigBody ® has been demonstrated by real surgery on two patients based on prior virtual operation results. Both subjects experienced excellent surgical outcomes with no residual nasal obstruction. Conclusions: This tool has great potential to aid surgeons in modeling potential surgical maneuvers, minimizing complications, and being confident that patients will receive optimal postoperative outcomes, validated by personalized CFD testing. Highlights: A new software tool DigBody ® for nasal surgery is introduced. This tool permits direct assessment of the operated cavity following virtual surgery by CFD simulation. The goal of this new surgery software is to allow the surgeon to directly modify the 3D nasal model. Before real surgery, we are also able to compare pre- and post-virtual surgery nasal CFD airflows. Its effectiveness on two patients has been demonstrated by real surgery handled by previous virtual surgery.